2021
DOI: 10.1186/s12954-021-00513-4
|View full text |Cite
|
Sign up to set email alerts
|

Municipal police support for harm reduction services in officer-led referrals of people who inject drugs in Tijuana, Mexico

Abstract: Background Police constitute a structural determinant of health and HIV risk of people who inject drugs (PWID), and negative encounters with law enforcement present significant barriers to PWID access to harm reduction services. Conversely, police may facilitate access via officer-led referrals, potentiating prevention of HIV, overdose, and drug-related harms. We aimed to identify police characteristics associated with support for officer-led referrals to addiction treatment services and syring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…This finding has many parallels to emerging research that examines how law enforcement officials may interact with SSPs and their clients. For example, a recent study found that police officers who endorsed SSPs were less likely to believe that SSP implementation increased risks for needlestick injury [ 33 ]. In addition, a 2019 study found that law enforcement officials who experienced a needlestick injury were more critical of SSPs, reporting that they believed SSPs enabled drug use [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding has many parallels to emerging research that examines how law enforcement officials may interact with SSPs and their clients. For example, a recent study found that police officers who endorsed SSPs were less likely to believe that SSP implementation increased risks for needlestick injury [ 33 ]. In addition, a 2019 study found that law enforcement officials who experienced a needlestick injury were more critical of SSPs, reporting that they believed SSPs enabled drug use [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These responders generally are social workers or behavioural/ mental health clinicians or specialists, with a particular focus on stabilizing individuals in crisis. Usually, these responders monitor police radios and are dispatched in response to very specific call types clearly identified as involving mental or behavioural health needs that do not involve the presence of a weapon at the time of dispatch (Baker et al, 2021;Blais & Brisebois, 2021;Lum et al, 2021). These teams are also dispatched for issues related to substance use and homelessness.…”
Section: Alternative Responsementioning
confidence: 99%
“…Individuals often cycle repetitively through these systems-from jails to emergency rooms and back again (Milgram et al, 2018). This results in a small number of individuals with unmet needs using an outsized proportion of public resources across systems (Baker et al, 2021;Milgram et al, 2018). For example, researchers in Camden, New Jersey, analyzed local hospital and arrest data to find that more than half of individuals arrested between 2010 and 2014 also made five or more visits to the emergency room during that same period.…”
Section: Introductionmentioning
confidence: 99%